Authorities in Early Modern Law Courts - Rossi, Guido (Edinburgh University Press, 2020)
Bringing together some of the most distinguished scholars in the field including John Ford, Javier García Martín, David Ibbetson, Annamaria Monti, Peter Oestmann, Heikki Pihlajamäki and Alain Wijffels, this volume looks at the comparative development of legal practice in the early modern period across Europe. Focusing deliberately on the impact of law courts on substantive law - and not on its systematisation by learned jurists - it studies similarities and differences in the development of the law across different jurisdictions. In doing so it evaluates whether and to what extent it is possible to consider this development as a unitary and truly European phenomenon. This collection re-evaluates current debates surrounding the development of civil law in the early modern period in the context of the grand narratives of European legal history and sets out to challenge current orthodox views about early modern civil law.